Correlating Selective Electrocatalysis of Dopamine and Ascorbic Acid Electrooxidation at Nanoporous Gold Surfaces with Structural-Defects. Issue 14 (1st January 2019) - Kumar, Abhishek; Gonçalves, Josué M.; Selva, Jéssica S. G.; Araki, Koiti; Bertotti, Mauro
Abstract : Interlinking kinetics of electrode processes of electroactive compounds with structural properties of the electrode materials like nanoporous gold (NPG) can be a smart strategy to design an electrocatalyst for specific applications. Accordingly, NPG materials electrochemically synthesized and characterized to confirm their structure and morphology were employed as platform to investigate the electrode reactions of ascorbic acid (AA) and dopamine (DA). A systematic study revealed that DA heterogeneous electron transfer (HET) rate is slower and independent of the electrode materials, whereas AA oxidation process becomes faster as a function of the NPG thickness. Such observations were correlated with changes in the mass transport and the specific surface interactions of AA and DA with changing film thickness of NPG. DA adsorbs strongly and the electrochemical process is essentially influenced by the larger surface area of the NPG film. On the other hand, AA interacts preferentially with the exposed high energy and more reactive (200), (220) and (311) crystalline facets of gold, which increase in thicker NPG films as demonstrated by High Resolution Transmission Electron Microscopy and X-Ray Diffraction, enhancing the HET rate.